Profitability Analysis of Urban Dairy Cattle Farming in Farmer Groups in Jakarta Metropolitan Area - Yusman Syaukat; Faroby Falatehan; Suprehatin Suprehatin; Tessa Magrianti (Agrisocionomics: Jurnal Sosial Ekonomi Pertanian, 2026)
Dairy cattle farming contributes significantly to global food security, yet research on urban dairy operations remains limited, particularly in metropolitan areas of developing countries where land scarcity and high operational costs present unique challenges. This study quantifies the profitability of smallholder dairy operations in Jakarta by examining production costs, revenue streams, return-cost ratios, and net profit margins under urban resource constraints. A survey conducted from October to November 2024 involving 56 active farmers used structured questionnaires and field observations. A Cobb-Douglas production framework analyzed through ordinary least squares regression identified determinants of milk output, complemented by descriptive examination of producer demographics, resource utilization, and economic indicators. Farmers averaged 49 years old with 13 years of formal education and 24 years of farming experience. Input allocation was found to be unbalanced, with forage and concentrates below recommended levels while tofu pulp and labor were excessive. Regression analysis indicated that lactating cow numbers and concentrate use significantly influenced milk production, while other inputs showed no significant effect. Feed, particularly tofu pulp, dominated the cost structure, with average annual production cost of IDR 280.2 million. Total annual revenue reached IDR 384.6 million, yielding net income of IDR 104.4 million. Urban dairy farming in Jakarta proved economically feasible with an R/C ratio of 1.37 and profitability of 37.27%. Metropolitan dairy production remains economically viable for small-scale operators through optimized feeding protocols, proactive animal healthcare, strategic policy support including input price stabilization and urban agricultural zoning, alongside revenue diversification for enhanced operational resilience.